The Use of 5-Hydroxymethylfurfural towards Fine Chemicals: Synthesis and Direct Arylation of 5-HMF-Based Oxazoles - da Rosa, Rafael; Grand, Lucie; Schenkel, Eloir P.; Sibelle Campos Bernardes, Lílian; Jacolot, Maïwenn; Popowycz, Florence (Synlett, 2021)
5-Hydroxymethylfurfural (5-HMF) is a renewable platform chemical used as a source for obtaining diverse fine chemicals. In this letter, we report the synthesis of 5-HMF-based oxazole compounds. While 5-HMF could be easily converted into the oxazole derivative through the Van Leusen reaction, the direct arylation step needed to access the final compounds was problematic at first. After optimization, a palladium-catalyzed procedure has been developed and used for the synthesis of a series of 33 derivatives. This article reports an extension of the late-stage CH arylation reaction as an application to the oxazole platform derived from biosourced 5-HMF. The challenges in the preparation of the derivatives containing some electron-withdrawing substituents were overcome by the use of a palladium-free method.
Keywords: 5-hydroxymethylfurfural; direct arylation; oxazole; bio-based; platform chemical